Design and Development of a Targeted Job Fair Information System for Vocational Education - Huriati Putri; Resmi Darni; Lativa Mursyida; Rizkayeni Marta (Universitas Negeri Padang, 2025)
The increasing demand for effective school-to-work transition mechanisms in vocational education highlights the need for integrated digital platforms. At State Vocational High School 2 Padang Panjang, the dissemination of job vacancy information and alumni data management remains manual, fragmented, and inefficient. Traditional communication channels, such as WhatsApp groups and direct phone calls, often fail to reach all alumni, while data collection via Google Forms lacks automation, scalability, and security. To address these challenges, this study developed a web-based Special Job Fair Information System using the Prototype development model. The system was implemented using the Laravel framework and MySQL database, allowing for real-time data management, secure job vacancy submissions, automated alumni tracking, and dynamic report generation. Performance testing using GTMetrix demonstrated strong system reliability, with a performance score of 94%, structure score of 97%, and favorable metrics including 1.5 seconds for Largest Contentful Paint (LCP), 0 milliseconds Total Blocking Time (TBT), and a Cumulative Layout Shift (CLS) score of 0. These results indicate a fast, stable, and responsive user experience. The system offers a scalable solution for improving graduate employability services in vocational education institutions, particularly in resource-constrained environments.